Duke Research at Pickett: The evolution of a free-standing research site partnering with communities toward health equity advancement - Laura Van Althuis; Sally Taylor; Debra Freeman; Stephanie Freel; Lynn Sutton; Kenisha Bethea; Leatrice Martin; Amanda McMillan; Diane Williams Garber; Keisha Bentley-Edwards; Nadine Barrett; Denise C. Snyder; et al. (Journal of Clinical and Translational Science)
While clinical research intends to improve health outcomes for all, access to research participation is often limited and inequitable. Geographic proximity is a recognized barrier, thus, systemic infrastructure solutions through federal programs including General Clinical Research Centers and Clinical and Translational Science Awards have sought to improve accessibility. Even with such support, academic medical centers often have limited clinical research-dedicated space apart from shared exam rooms in difficult-to-navigate hospitals or clinics. In 2019, the Duke University School of Medicine looked beyond its medical center campus to identify free-standing sites within Durham communities for participant study visits. Catalyzed by the COVID-19 pandemic, Duke Research at Pickett, a 22 000-square-foot building with a laboratory, 30 exam rooms, and on-site parking, opened in October 2020 to support vaccine and treatment trials. Upon the lifting of many COVID-19 restrictions, and in partnership with the Research Equity and Diversity Initiative (READI) Community Advisory Council, the building was transformed to encourage community gatherings, education, and training programs. To date, Duke Research at Pickett has hosted 2692 participants in 78 research trials and 14 community-engaged activities.